Organoid Technology: A Reliable Developmental Biology Tool for Organ-Specific Nanotoxicity Evaluation - Prasad, Minakshi; Kumar, Rajesh; Buragohain, Lukumoni; Kumari, Ankur; Ghosh, Mayukh (Frontiers in Cell and Developmental Biology, 2021)
Engineered nanomaterials are bestowed with certain inherent physicochemical properties unlike their parent materials, rendering them suitable for the multifaceted needs of state-of-the-art biomedical, and pharmaceutical applications. The log-phase development of nano-science along with improved “bench to beside” conversion carries an enhanced probability of human exposure with numerous nanoparticles. Thus, toxicity assessment of these novel nanoscale materials holds a key to ensuring the safety aspects or else the global biome will certainly face a debacle. The toxicity may span from health hazards due to direct exposure to indirect means through food chain contamination or environmental pollution, even causing genotoxicity. Multiple ways of nanotoxicity evaluation include several in vitro and in vivo methods, with in vitro methods occupying the bulk of the “experimental space.” The underlying reason may be multiple, but ethical constraints in in vivo animal experiments are a significant one. Two-dimensional (2D) monoculture is undoubtedly the most exploited in vitro method providing advantages in terms of cost-effectiveness, high throughput, and reproducibility. However, it often fails to mimic a tissue or organ which possesses a defined three-dimensional structure (3D) along with intercellular communication machinery. Instead, microtissues such as spheroids or organoids having a precise 3D architecture and proximate in vivo tissue-like behavior can provide a more realistic evaluation than 2D monocultures. Recent developments in microfluidics and bioreactor-based organoid synthesis have eased the difficulties to prosper nano-toxicological analysis in organoid models surpassing the obstacle of ethical issues. The present review will enlighten applications of organoids in nanotoxicological evaluation, their advantages, and prospects toward securing commonplace nano-interventions.